Quantitative end qualitative analysis of the electrical activity of rectus abdominis muscle portions - De Faria Negrão Filho, Rúben; Bérzin, F.; Da Cunha Souza, G. (My University, 2003)
The purpose of this study was to investigate the electrical behavior pattern of the Rectus abdominis muscle by qualitative and quantitative analysis of the electromyographic signal obtained from its superior, medium and inferior portions during dynamic and static activities. Ten voluntaries (aged X = 17.8 years, SD = 1.6) athletic males were studied without history of muscle skeletal disfunction. For the quantitative analysis the RMS (Root Mean Square) values obtained in the electromyographic signal during the isometric exercises were normalized and expressed in maximum voluntary isometric contraction percentages. For the qualitative analysis of the dynamic activity the electromyographic signal was processed by full-wave rectification, linear envelope and normalization (amplitude and time), so that the resulting curve of the processed signal was submitted to descriptive graphic analysis. The results of the quantitative study show that there is not a statistically significant difference among the portions of the muscle. Qualitative analysis demonstrated two aspects: the presence of a common activation electric pattern in the portions of Rectus abdominis muscle and the absence of significant difference in the inclination angles in the electrical activity curve during the isotonic exercises.
Keywords: Electromyography; Exercise; Rectus abdominis muscle